Repellency Potential, Chemical Constituents of Ocimum Plant Essential Oils, and Their Headspace Volatiles against Anopheles gambiae s. s., Malaria Vector - Jonathan Osei-Owusu; William K. Heve; Owusu Fordjour Aidoo; Maxwell Jnr Opoku; Joseph Apau; Kodwo Ninsin Dadzie; Bright Yaw Vigbedor; Kwaafo Akoto Awuah-Mensah; Margaret Appiah; Akwasi Acheampong; Michael Birkett; Antony Hooper (Journal of Chemistry)
African malaria mosquitoes (Anopheles gambiae sensu stricto) transmit a malaria parasite (Plasmodium falciparum) to humans. The current control strategies for the vector have mainly focussed on synthetic products, which negatively impact the environment and human health. Given the potential use of environmentally friendly plant-derived volatiles as a control, this work aims to examine and compare the repellency potential of essential oils and headspace volatiles from Ocimum gratissimum, Ocimum tenuiflorum, and Ocimum basilicum and their chemical compositions. The repellency potential and chemical composition of the plants were achieved by using the protected arm-in-cage method and gas chromatography-mass spectrometry (GC-MS) analysis. Among the three Ocimum species, both the essential oils and the headspace volatiles from O. tenuiflorum achieved the longest repellency time lengths of 90–120 minutes. One hundred and one (101) chemical constituents were identified in the headspace volatiles of the three Ocimum spp. Nonetheless, (−)-camphor, (E)-γ-bisabolene, terpinolene, β-chamigrene, cubedol, (E)-farnesol, germacrene D-4-ol, viridiflorol, γ-eudesmol, tetracyclo [6.3.2.0 (2,5).0(1,8)] tridecan-9-ol, 4,4-dimethyl, α-eudesmol, isolongifolol, and endo-borneol were unique only to O. tenuiflorum headspace volatiles. Either essential oils or headspace volatiles from O. tenuiflorum could offer longer protection time length to humans against An. gambiae. Though field studies are needed to assess the complementarity between the chemical constituents in the headspace volatiles of O. tenuiflorum, our observations provide a foundation for developing effective repellents against An. gambiae.